Efficacy and Safety of Ablation for Symptomatic Atrial Fibrillation in Elderly Patients: A Meta-Analysis - Lee, Wei-Chieh; Wu, Po-Jui; Chen, Huang-Chung; Fang, Hsiu-Yu; Liu, Ping-Yen; Chen, Mien-Cheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Age affects the efficacy of pharmacological treatment for atrial fibrillation (AF). Catheter ablation, including radiofrequency (RF) or cryoballoon ablation, is an effective strategy for symptomatic AF. This meta-analysis aimed to analyze the efficacy and safety of AF ablation in elderly patients with AF compared to non-elderly patients with AF. Methods: We searched several databases for articles published between January 1, 2008, and March 31, 2020. Eighteen observational studies with 21,039 patients were analyzed. Data including recurrence of AF or atrial tachyarrhythmia (ATA), complications, procedural time, and fluoroscopic time were compared between the elderly and non-elderly groups. Results: The elderly patients had significantly higher incidences of recurrent AF or ATA after AF ablation compared to the non-elderly patients (<60 years old) (odds ratio [OR], 1.21; 95% confidence interval [CI], 1.11-1.33). The elderly patients had significantly higher incidences of complications of AF ablation compared to the non-elderly patients (OR, 1.37; 95% CI, 1.14-1.64). However, elderly AF patients with age ≥75 years old had similar incidences of recurrent AF or ATA and complications after AF ablation compared to non-elderly patients with AF. Conclusions: The elderly patients had significantly higher incidences of recurrent AF or ATA and complications after ablation for non-paroxysmal AF compared to non-elderly patients with AF (<60 years old), except in patients ≥75 years old.